Answer

Verified

418.2k+ views

**Hint:**We will first assume $x = r\cos \theta $ and $y = r\sin \theta $ and find r according to it. After that we will just put in the required values and modify to get the answer.

**Complete step-by-step answer:**

We have to write $r = 2a\cos \theta $ into a Cartesian equation.

Let us first of all assume that $x = r\cos \theta $ and $y = r\sin \theta $ in the above equation.

Since we assumed that $x = r\cos \theta $. On dividing this by r on both the sides, we will get:-

\[ \Rightarrow \dfrac{x}{r} = \dfrac{{r\cos \theta }}{r}\]

Is we cut off r from the right hand side in both numerator and denominator, we will then obtain the following expression:-

\[ \Rightarrow \dfrac{x}{r} = \cos \theta \] ……………(1)

Now, since we assumed that $x = r\cos \theta $ and $y = r\sin \theta $.

Squaring both, we will then obtain:-

$ \Rightarrow {x^2} = {\left( {r\cos \theta } \right)^2}$ and ${y^2} = {\left( {r\sin \theta } \right)^2}$

Simplifying the calculations by opening the squares in above expression, we will then obtain the following expression:-

$ \Rightarrow {x^2} = {r^2}{\cos ^2}\theta $ and ${y^2} = {r^2}{\sin ^2}\theta $

Adding both the expressions from the above line, we will get:-

\[ \Rightarrow {x^2} + {y^2} = {r^2}{\cos ^2}\theta + {r^2}{\sin ^2}\theta \]

Taking square of r common on the right hand side, we will then obtain:-

\[ \Rightarrow {x^2} + {y^2} = {r^2}\left( {{{\cos }^2}\theta + {{\sin }^2}\theta } \right)\]

Since, we know that \[{\cos ^2}\theta + {\sin ^2}\theta = 1\]. Using this in the above equation, we will then obtain the following expression:-

\[ \Rightarrow {x^2} + {y^2} = {r^2}\] …………………..(2)

Now, considering the equation given to us which is $r = 2a\cos \theta $.

Putting the equation (1) in it, we will then obtain:-

$ \Rightarrow r = 2a \times \dfrac{x}{r}$

Taking r from division in the right hand side to multiplication in the left hand side and re – arranging the terms to obtain the following expression:-

$ \Rightarrow x = 2a{r^2}$

Putting the equation (2) in the above expression to obtain the following expression:-

\[ \Rightarrow x = 2a\left( {{x^2} + {y^2}} \right)\]

**Hence, we have the required Cartesian equation of $r = 2a\cos \theta $ as \[x = 2a\left( {{x^2} + {y^2}} \right)\].**

**Note:**

The students must note that in the starting steps when we divided x by r in order to the required modification, we could divide because r is non zero because if r would have been zero, either a is zero which makes our equation as the point of origin or we have the angle theta equal to 90 degrees which is also very much fixed. Therefore, we have r is not equal to zero and we divided the whole equation by it. We can never divide any equation by 0 and we cannot multiply any equation by 0 as well.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Mark and label the given geoinformation on the outline class 11 social science CBSE

When people say No pun intended what does that mea class 8 english CBSE

Name the states which share their boundary with Indias class 9 social science CBSE

Give an account of the Northern Plains of India class 9 social science CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

Trending doubts

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Which are the Top 10 Largest Countries of the World?

One cusec is equal to how many liters class 8 maths CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

The mountain range which stretches from Gujarat in class 10 social science CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths